2015
DOI: 10.17015/ejbe.2015.016.08
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Brand on Consumer Preferences: A study in Turkmenistan

Abstract: Using a measurement model of brand name and consumer preferences, this study aims to investigate the effects of brand name on consumer preferences in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 16 publications
(23 reference statements)
1
13
0
Order By: Relevance
“…Isik and Yasar [11] stated that brand preference is the extension of consumer favor toward the designed services provided by the specific company when compared with services provided by other companies presented in a consideration set. Self-image congruity was a very strong predictor of consumer brand preferences and a good predictor of consumer satisfaction.…”
Section: Hypothesis 1 (H1) the Smmes Of The Local Bangladeshi Fashiomentioning
confidence: 99%
See 1 more Smart Citation
“…Isik and Yasar [11] stated that brand preference is the extension of consumer favor toward the designed services provided by the specific company when compared with services provided by other companies presented in a consideration set. Self-image congruity was a very strong predictor of consumer brand preferences and a good predictor of consumer satisfaction.…”
Section: Hypothesis 1 (H1) the Smmes Of The Local Bangladeshi Fashiomentioning
confidence: 99%
“…Thus, brand preference is used as the second measurement dimension for our study. According to Isik and Yasar [11], brand preference is the extension of consumer favor toward the designed services provided by a specific company in comparison with services provided by other companies presented in a consideration set. Brand associations related to functions represent a considerable degree of abstraction compared to those that refer to attributes; thus, the former is more accessible and stays longer in the memory of consumers than the latter [12].…”
Section: Introductionmentioning
confidence: 99%
“…As pointed out by Szablowski and Resenberg (2015), brand preference is driven by new and engaging media that catch people on the run. To ensure that a brand is preferred to others, identifying the target market, managing the legalities, securing celebrity endorsement among others have been advocated by scholars such as Karen (2011), Ebrahim (2013 and Isik and Yasar (2015). Fournier (1998) once pointed out that a brand in fact is simply a collection of perceptions that are held in the minds of the consumers and have no objective existence at all other than through the activities of the managers that administer it.…”
Section: Concept Of Brand Preferencementioning
confidence: 99%
“…The stronger the brand position is in the consumer"s mind, according to Simon (2011), the more essential source of differentiation it becomes, and this a fundamental competitive advantage. According to Isik and Yasar (2015), brand preference is regarded as a key step in consumer decision making, involving elements of choice. In establishing brand preference, consumers compare and rank different brands by focusing on their uniqueness.…”
Section: Concept Of Brand Preferencementioning
confidence: 99%
“…The basic hypothesis is there is need for visual attention in order to properly bind features of an object (Wolfe, 2020). Consumer preference had been described as consisting of a group of assumptions which permit a consumer to classify different types of products following levels of utility or holistic satisfaction or dissatisfaction of consuming particular goods or services (Isik and Yasar, 2015). In doing this, earlier studies have indicated that consumers usually display a certain ambivalent approach when exposed to products that are novel to them or ones they are unaccustomed to.…”
Section: Introductionmentioning
confidence: 99%